GENETIC PURITY ASSESSMENT IN LINSEED (LINUM USITATISSIMUM L.) VARIETIES USING MICROSATELLITE MARKERS - PREETI SINGH; NANDAN MEHTA; ABHINAV SAO (The Bioscan, 2015)
The present investigation was undertaken in the Department of Genetics and Plant Breeding, IGKV, Raipur, India during Rabi 2012-13 and 2013-14 season. The present investigation was carried out with the objectives to identify informative SSR marker allele (s) for fingerprinting popular linseed cultivars, and to identify specific SSR markers in seed genetic purity assessments. A set of 38 SSR markers located across the 30 chromosomes of linseed were used, out of which 28 SSR markers were observed to be polymorphic for cultivars considered in the study. These loci were screened in breeder seed of four popular cultivars of linseed. Out of These Thirty-eight microsatellite markers six microsatellite (LU-1,LU-7,LU-8,LU-9,LU-24,LU-25 ) markers were found polymorphic which are used for fingerprinting in population. Based on the polymorphic status, 6 SSR markers were found to be informative for discriminating the genotypes and showed a total of 24 alleles. To validate the utility of the SSR markers in genetic purity assessment, seed lots of R 552, Deepika, Indira Alsi 32 and RLC 92 were assessed for their genetic purity using both SSR marker analysis and 18 morphological characters in a grow-out test (GOT). The results indicated practical utility of the SSR markers in assessing the genetic purity of the linseed cultivars and their fingerprinting. Abbreviations: CTAB-Cetyl Trimethyl Ammonium Bromide, DUS-Distinctness Uniformity Stability, PAGE-Poly Acryl-amide Gel Electrophoresis, PCR-Polymerase Chain Reaction, PIC-Polymorphic Information Content, SPS- Single Plant Selection, SSR-Simple Sequence Repeats, UPOV-Union for Protection of New Plant Varieties.